2005
DOI: 10.1007/s10350-004-0918-z
|View full text |Cite
|
Sign up to set email alerts
|

Stapled Hemorrhoidopexy vs. Harmonic Scalpel™ Hemorrhoidectomy: A Randomized Trial

Abstract: Stapled hemorrhoidopexy is a safe and effective procedure for Grade III hemorrhoidal disease. Patients derive greater short-term benefits of reduced pain, shorter length of stay, and earlier resumption to work. Long-term follow-up is necessary to determine whether these initial results are lasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 33 publications
2
76
0
Order By: Relevance
“…The mean operative time in our study was 37.23 ± 6.287 in group A (Electrocautery) while in group B, it was 32.24 ± 7.334 minutes [Stapler (PPH Gun)]. This is comparable to the results by Chung CC et al (13) in which the mean operative time with Electrocautery is 36 ± 3 minutes and with Ultrasonic Harmonic Scalpel is 30 ± 4 minutes. In the study by Tsunoda et al (12) , median operative time was 16 (95% confidence interval: 14.6-18.2) minutes in electrocautery group while in harmonic scalpel group it was 31 minutes (95% confidence interval:28.1-35.3), with p-value ≤0.0001.…”
Section: Discussionsupporting
confidence: 80%
“…The mean operative time in our study was 37.23 ± 6.287 in group A (Electrocautery) while in group B, it was 32.24 ± 7.334 minutes [Stapler (PPH Gun)]. This is comparable to the results by Chung CC et al (13) in which the mean operative time with Electrocautery is 36 ± 3 minutes and with Ultrasonic Harmonic Scalpel is 30 ± 4 minutes. In the study by Tsunoda et al (12) , median operative time was 16 (95% confidence interval: 14.6-18.2) minutes in electrocautery group while in harmonic scalpel group it was 31 minutes (95% confidence interval:28.1-35.3), with p-value ≤0.0001.…”
Section: Discussionsupporting
confidence: 80%
“…Faecal urgency was reported after CH [35] in the postoperative period [35,37,41]. There was no difference at 12 months and beyond (OR 1.04; 95% CI: 0.36, 3.03; P = 0.94; five RCTs) [21,24,33,34,43].…”
Section: Complicationsmentioning
confidence: 99%
“…3) [12,22,[25][26][27][28]30,32,[35][36][37][38][39][40][41][42]. Significant heterogeneity was observed between studies (P = 0.003; I 2 = 57.8).…”
Section: Bleedingmentioning
confidence: 99%
“…The amount of intraoperative blood loss in my study was 8.000 ± 3.539 ml in Electrocautery group, while in Stapler Hemorrhoidopexy group; it was 6.29 ± 3.271 ml. In the study by Chung CC et al (13) , the amount of blood loss in Stapler group was 7 ± 3 ml while in Ultrasonic Harmonic Scalpel group; this was 10 ± 4 ml. In the study by Tsunoda et al (12) , reduced intraoperative blood loss was observed in the diathermy group; mean blood loss is 9 ± 3ml versus harmonic scalpel group, mean blood loss 7 ± 3 ml with p-value < 0.001.…”
Section: Discussionmentioning
confidence: 88%